Effect of external magnetic fields on various free-surface flows. (26th November 2008) - Tagawa, Toshio; Ozoe, Hiroyuki
Liquid-gas free-surface flows in the presence of gravity, surface tension and magnetic field are numerically studied. Two phases (both liquid and gas) are assumed to be an incompressible, immiscible, Newtonian fluid and both viscous dissipation and Joule heating are neglected. Thermal convection due to buoyancy and thermo-capillary effects is not taken into account. The numerical results reveal significant difference in the free-surface flows depending on the applied magnetic field not only for the electric conducting fluids such as mercury and gallium but also for ordinary non-conducting fluids such as water and air.